Become your own boss in 12 months : a month-by-month guide to a business that works - Emerson, Melinda F. (Petaling Jaya : Advantage Quest Publications, 2013)
A guide, in a month-by-month format, to help a person start a new business.
Includes bibliographical references and index.
Keywords: Self-employed.; New business enterprises -- Management